Side Effects of Endocrine Therapy Are Associated With Depression and Anxiety in Breast Cancer Patients Accepting Endocrine Therapy: A Cross-Sectional Study in China - Zhao, Rong; Liu, Hulin; Gao, Jinnan (Frontiers in Psychology, 2022)
Objective: Hormone positive breast cancer patients bear side effects of endocrine therapy and that may be related to depression and anxiety. We sought to find an association between mental health and side effects of endocrine therapy. Methods: A total of 398 patients participated. Sociodemographic, disease profile, and side effects questionnaires were administered. We screened for depressive and anxiety disorders by using the SDS (Self-Rating Depression Scale) and SAS (Self-Rating Anxiety Scale). Results: The prevalence of depression and anxiety in our study were 33.4% (133) and 13.3% (53), respectively. Depression was linked to education level (≤ 8 years, OR = 3.59, 95% CI: 2.22-5.78), night sweats (yes, OR = 1.90, 95% CI: 1.17-3.09), vaginal dryness (yes, OR = 2.22, 95% CI: 1.19-4.16), and fatigue (yes, OR = 1.94, 95% CI: 1.21-3.11); anxiety was associated with education level (≤ 8 years, OR = 3.13, 95% CI: 1.62-6.08), time to diagnosis (≤ 3 years, OR = 2.14, 95% CI: 1.13-4.07), osteopenia (yes, OR = 2.43, 95% CI: 1.26-4.70), loss of hair (yes, OR = 2.80, 95% CI: 1.10-7.15), and fatigue (yes, OR = 2.89, 95% CI: 1.54-5.43). A stratified analysis according to age (≤ 45 years and > 45 years) was performed as an exploratory. None of factor-age interactions was statistically significant. Conclusions: Side effects of ET were significantly associated with anxiety and depression. Side effects deserve greater emphasis and clinical interventions are needed to reduce anxiety and depression in breast cancer patients accepting ET.